LEUCISM IN PLUMBEOUS RAIL (PARDIRALLUS SANGUINOLENTUS: RALLIDAE) IN THE WETLAND OF LUCRE-HUACARPAY THE SOUTHERN ANDES OF PERU - Atauchi, Pavel J. (2015)
The color pattern of a case of leucism is described in an individual of Plumbeous rail (Pardirallussanguinolentus), in the Wetland of Lucre-Huacarpay southern Andes of Perú.